Impacts of visual-acoustic-thermal environments on human perception of coastal greenways in temperate oceanic monsoon climate zones - Ruirui Zhu; Yefan Wang; Ruixin Xue; Shuo Teng; Bowen Niu; Haoyang Mu (Case Studies in Thermal Engineering)
The visual, acoustic, and thermal environments significantly influence human perception, nevertheless, their cumulative impacts in coastal greenways under moderate oceanic monsoon climate remain unexplored. Therefore, this research examined the impact of visual-acoustic-thermal environments on human perception through objective environmental measurements and subjective perception questionnaire surveys (n = 600), taking the Qingdao coastal greenway as a case study. The results indicated a significant association between the visual comfort vote (VCV) and both the overall comfort vote (OCV) (χ2 = 288.17, p < 0.001) and overall satisfaction (OS) (χ2 = 310.65, p < 0.001). The Acoustic Comfort Vote (ACV) was adversely impacted by LAeq (r = −0.318) and was influenced by mechanical and human sounds, however natural sounds can alleviate noise effects. The thermal sensation vote (TSV) exhibited consistent correlations with OCV (R2 = 0.78) and the overall satisfaction (OS) (R2 = 0.84). Linear regression analysis revealed that TCV had the most significant impact on OCV: OCV = 0.27 × VCV +0.17 × ACV +0.40 × TCV +0.29. The results indicate that thermal comfort is the primary concern and underscore the significance of an integrated visual-acoustic-thermal design. This research can offer theoretical foundations for the design and optimization of coastal greenways.